The Influence of Motivation and Work Culture on Employee Performance at the Isotope and Radiation Application Center - National Nuclear Energy Agency, Lebak Bulus, South Jakarta - Priska Larasati Ramadhany; Soelaiman Sukmalana; Titi Titi; Lungguh Jatmika; Tini Supartini (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study concludes that leadership and work discipline significantly affect employee performance in a beauty clinic in Bandung. Both variables have been demonstrated to enhance staff productivity and work efficiency significantly. Effective leadership fosters a supportive work environment wherein individuals feel encouraged, directed, and inspired to attain optimal outcomes. An effective leader provides clear guidance and fosters open communication with the team, enabling people to execute their tasks confidently. Moreover, work discipline is a crucial element in enhancing performance. Effective discipline signifies employee adherence to regulations and obligations inside the workplace. This condition is shown in punctuality, achievement of job objectives, and persistence in task execution. Work discipline is crucial for upholding high and consistent performance levels in a clinical setting, where patient care quality significantly influences reputation and operations. The correlation between leadership and work discipline indicates that effective leadership can foster enhanced employee discipline. Leaders who can implement regulations decisively yet equitably will foster a disciplined work environment, inspiring employees to adhere to relevant protocols. Employees who perceive appreciation and encouragement from their bosses typically exhibit a more disciplined work ethic. Consequently, both are interrelated and mutually enhance one another in promoting superior performance. This study's findings underscore the significance of clinic management in fostering an inclusive leadership style and promoting a culture of discipline. Enhancing employee performance can be accomplished not only via effective leadership but also through the establishment of consistent disciplinary measures. Consequently, strategic measures encompassing leadership development and enhancing work discipline are necessary. A Beauty Clinic in Bandung can enhance patient service quality by optimizing human resource management, emphasizing leadership development, and rigorous discipline enforcement.